Socio-Economic Activities of the Engineering Corps of the Polish Army in the Years 1945–1956 - Pietrygała, Robert (Social consequences of war, 2024)
The second half of the 20th century was marked by numerous wars and disasters, which consequently caused enormous human, financial, and material losses. Engineering troops played a decisive role in the activities in the face of crises and the elimination of their consequences. This role was mainly determined by the specialized equipment and the adaptation of these formations to this type of operations, which are referred to as non-military operations. The main tasks of the engineering units in 1945–1956 included in particular clearing the territory of the Polish state of the remnants of mines, unexploded ordnance, and dangerous objects, participation in the elimination of natural disasters, and participation in works for the benefit of the national economy and the Ministry of National Defence. Moreover, the soldiers of these troops took an active part in clearing the country of debris, came to the aid of harvesting operations, digging up agricultural produce, assisted in clean-up work, helped in fire extinguishing, and cleared snow from roads and railways. All of the above issues have been synthesized for this article.